1999
DOI: 10.1097/00003072-199912000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m Sestamibi Scintimammography in the Mammographically Dense Breast

Abstract: Six examples from our clinical experience show the usefulness of Tc-99m sestamibi imaging in patients with mammographically dense breasts. The ability to identify a malignancy or its absence supports the continued use of this procedure in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…These falsepositive readings might occur because of markedly increased metabolic activity, allowing accumulation of the radioisotope in these areas or because of the hypercellularity of the breast lesions with or without atypical cells. 2,11,13,16,17 There were two cases reported as false negative on SM examination that were diagnosed as malignant on histopathological examination. Of these cases, one proved to be infiltrating ductal carcinoma, which appeared as microcalcification on mammography without mass lesion, and the other was diagnosed as mucinous carcinoma, which looked like a cystic mass with an irregular thick wall on ultrasound (Table 3).…”
Section: Of the 25 Malignant Cases With 27 Lesions 25 Lesions (92%)mentioning
confidence: 99%
See 2 more Smart Citations
“…These falsepositive readings might occur because of markedly increased metabolic activity, allowing accumulation of the radioisotope in these areas or because of the hypercellularity of the breast lesions with or without atypical cells. 2,11,13,16,17 There were two cases reported as false negative on SM examination that were diagnosed as malignant on histopathological examination. Of these cases, one proved to be infiltrating ductal carcinoma, which appeared as microcalcification on mammography without mass lesion, and the other was diagnosed as mucinous carcinoma, which looked like a cystic mass with an irregular thick wall on ultrasound (Table 3).…”
Section: Of the 25 Malignant Cases With 27 Lesions 25 Lesions (92%)mentioning
confidence: 99%
“…1 During the last decade, various studies have shown the use of scintimammography (SM) in evaluating patients with mammographically dense breasts, which present difficulties in interpreting mammograms. 2 The sensitivity of SM ranges from 60 to 96% and specificity ranges from 67 to 100%. 3,4 This technique is safe, easy to interpret and has excellent interobserver agreement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation